2018
DOI: 10.15407/fz64.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic hypomelatoninemia on carbohydrate and lipid metabolism of rats kept on western diet

Abstract: Досліджували вплив гіпомелатонінемії, індукованої цілодобовим освітленням щурів інтенсивністю 1500 лк протягом 60 діб, на вуглеводний і ліпідний обмін за умов призначення висококалорійної вуглеводно-ліпідної дієти (20 %-й розчин фруктози та відповідний раціон). Виявлено, що за цих умов зменшувалася концентрація мелатоніну у сироватці крові на 55,6 % порівняно з результатом, отриманим при окремому цілодобовому освітленні. У тварин спостерігалися більш глибокі метаболічні порушення, притаманні синдрому інсулінор… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
4
0
6
Order By: Relevance
“…Earlier, we demonstrated that the development of hypomelatoninaemia naturally occurs in rats due to long-term RCL exposure and does not manifest when the rats are kept on HFHLD. However, when these factors act together, the melatonin level is significantly reduced compared to the effects resulting from the separate use of the above-mentioned factors [ 7 ]. This confirms the ability of alimentary factors under certain conditions to influence melatonin secretion, which was discovered by other researchers [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier, we demonstrated that the development of hypomelatoninaemia naturally occurs in rats due to long-term RCL exposure and does not manifest when the rats are kept on HFHLD. However, when these factors act together, the melatonin level is significantly reduced compared to the effects resulting from the separate use of the above-mentioned factors [ 7 ]. This confirms the ability of alimentary factors under certain conditions to influence melatonin secretion, which was discovered by other researchers [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have found out that the simultaneous effect of RCL and HFHLD leads to more marked metabolic disorders, such as LPO, and a decrease in the general antioxidant blood potential in the blood of rats, hyperinsulinaemia, hypo-α-lipoproteinaemia, hypertrialcylglycerolaemia, and increased visceral fat mass, in comparison with the animals kept on the HFHLD only [ 7 ]. This study demonstrated that resveratrol administered under RCL and HFHLD reduces the MDA-TBA 2 level and its increment over 1.5-h incubation in pro-oxidant ascorbate-iron buffer that points out the LPO restrain and growth in general antioxidant blood potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Розвиток гіпомелатонінемії при цілодобовому освітленні (ЦО) щурів посилюється призначенням щурам висококалорійного вуглеводно-ліпідного раціону [8]. Проте відновлення вмісту мелатоніну при його екзогенному введенні суттєво не впливає на індекс інсулінорезистентності HOMA-IR (Homeostasis Model Assessment of Insulin Resistance) та лише частково обмежує гіпер-глікемію, дисліпопротеїнемію та продукцію активних форм кисню й азоту (АФК і АФА відповідно) в тканинах скелетних м'язів і печінки [9].…”
Section: вступunclassified